Economic Policy Analysis of the "Taiwan Miracle" and Why Indonesia Needs to Learn It? - Ganinduto, Dico M (Socio-political Communication and Policy Review, 2025)
This study aims to analyze the role of economic policy and institutional capacity in driving Taiwan's economic growth in the period 1953–1982, and to compare the development experience with Indonesia during the same period. This study uses a qualitative comparative study method based on primary and secondary literature, including Thomas B. Gold's work "State and Society in the Taiwan Miracle" and various sources on Indonesian economic policy during the New Order era. The data used include statistics on economic growth, industrial structure, investment, and social indicators from both countries. The results show that Taiwan has succeeded in achieving high and sustainable economic growth through agrarian reform, export orientation, large investments in education and infrastructure, and the development of dynamic SMEs. Meanwhile, Indonesia's economic growth is more driven by natural resource exports and is less supported by deep structural transformation, making it vulnerable to fluctuations in global commodity prices and social inequality. These findings emphasize the importance of a proactive state role, strengthening institutional capacity, and synergy between the state and the market in creating inclusive and sustainable economic development.